Malt1 deficient mice develop osteoporosis independent of osteoclast‐intrinsic effects of Malt1 deficiency. Issue 4 (16th July 2019) - Monajemi, Mahdis; Fisk, Shera; Pang, Yvonne C. F.; Leung, Jessica; Menzies, Susan C.; Ben‐Othman, Rym; Cai, Bing; Kollmann, Tobias R.; Rozmus, Jacob; Sly, Laura M.
Abstract: This study tested the hypothesis that mucosa associated lymphoid tissue 1 (Malt1) deficiency causes osteoporosis in mice by increasing osteoclastogenesis and osteoclast activity. A patient with combined immunodeficiency (CID) caused by MALT1 deficiency had low bone mineral density resulting in multiple low impact fractures that was corrected by hematopoietic stem cell transplant (HSCT). We have reported that Malt1 deficient Mϕs, another myeloid cell type, are hyper‐responsive to inflammatory stimuli. Our objectives were to determine whether Malt1 deficient mice develop an osteoporosis‐like phenotype and whether it was caused by Malt1 deficiency in osteoclasts. We found that Malt1 deficient mice had low bone volume by 12 weeks of age, which was primarily associated with reduced trabecular bone. Malt1 protein is expressed and active in osteoclasts and is induced by receptor activator of NF‐κB ligand (RANKL) in preosteoclasts. Malt1 deficiency did not impact osteoclast differentiation or activity in vitro. However, Malt1 deficient ( Malt1 −/− ) mice had more osteoclasts in vivo and had lower levels of serum osteoprotegerin (OPG), an endogenous inhibitor of osteoclastogenesis. Inhibition of Malt1 activity in Mϕs induced MCSF production, required for osteoclastogenesis, and decreased OPG production in response to inflammatory stimuli. In vitro, MCSF increased and OPG inhibited osteoclastogenesis, but effects were not enhanced in Malt1 deficient osteoclasts. These data support the hypothesis that Malt1 deficient mice develop an osteoporotic phenotype with increased osteoclastogenesis in vivo, but suggest that this is caused by inflammation rather than an effect of Malt1 deficiency in osteoclasts. Abstract : Malt1 deficient mice develop osteoporosis characterized by increased numbers of osteoclasts in vivo but Malt1 deficiency does not impact osteoclast differentiation or activity directly.